The continuity of the extractivist development model in Peru - Lust, Jan (2020)
The growth of the exports of the country natural resources and foreign investment in the extractivist sectors are crucial for the development of Peruvian economy. Since the 1990s, the economic development model has been based on the export of commodities and the markets deregulation. In this article we argue that the continuity of the extractivist development model of the country is the consequence of the interaction between the objective and subjective conditions of the Peruvian capitalist development. The analysis of the objective conditions focuses on the role of the country in the international division of labor, the relation between this role and the economic and corporate structure of Peru, and the functionality of the extractivist development model for the Peruvian State. In the case of the subjective conditions, the force of political left, the workers movement and the social movements against the mining capital are analyzed.  The weakness of subjective conditions makes it impossible to change the objective conditions.